Pengelolaan Wisata pada Kawasan Strategis Pariwisata Nasional di Padang - Eliza, Yulina; Maryanti, Sri; Muslim, Irwan; Andria, Yass; Cahyadi, Irwan (Jurnal Ilmiah Pengabdian dan Inovasi, 2023)
The city of Padang has great tourism potential and is part of the KSPN. Therefore, community service activities aim to prepare the tourism management community. The method used in strengthening community capacity is contextual teaching and learning (TCL) to connect material with real conditions that exist in partner communities, especially for targeting tourism actors and Pokdarwis. The service is carried out in two stages and ends with an evaluation. Based on the evaluation results, participants not only know but also have the ability to identify, select procedures, and solve problems related to tourism management. Community service activities produce solutions to community problems regarding the limited understanding of KSPN and tourism management. Furthermore, the community needs to get assistance in designing and implementing creative tourism strategies with participatory methods. calculation of the level of achievement of respondents. The results of this study indicate that overall, the attractiveness of City Tourism is still being developed, and also strengthened by a tourist questionnaire which shows the ability of Padang City Tourism attractiveness.